Measuring anticholinergic drug exposure in older community‐dwelling Australian men: a comparison of four different measures. (6th July 2015) - Pont, Lisa G.; Nielen, Johannes T. H.; McLachlan, Andrew J.; Gnjidic, Danijela; Chan, Lewis; Cumming, Robert G.; Taxis, Katja
Abstract : Aims: Anticholinergic drug exposure is associated with adverse outcomes in older people. While a number of tools have been developed to measure anticholinergic drug exposure, there is limited information about the agreement and overlap between the various scales. The aim of this study was to investigate the agreement and overlap between different measures of anticholinergic drug exposure in a cohort of community‐dwelling older men. Methods: A cross‐sectional study was used to compare anticholinergic drug exposure calculated using the Anticholinergic Risk Scale (ARS), the Anticholinergic Drug Scale (ADS), the Anticholinergic Cognitive Burden (ACB) and the Drug Burden Index anticholinergic subscale (DBI‐ACH) in a cohort of community‐dwelling men aged 70 years and older ( n = 1696). Statistical agreement, expressed as Cohen's kappa (κ), between these measurements was calculated. Results: Differences were found between the tools regarding the classification of anticholinergic drug exposure for individual participants. Thirteen percent of the population used a drug listed as anticholinergic on the ARS, 39% used a drug listed on the ADS and the ACB, and 18% of the population used one or more anticholinergic drugs listed on the DBI‐ACH. While agreement was good between the ACB and ADS (κ = 0.628, 95% CI 0.593, 0.664), little agreement was found between remaining tools (κ = 0.091–0.264). Conclusions: With the exception of the ACB and ADS, there was poor agreement regarding anticholinergic drug exposure among the four tools compared in this study. Great care should be taken when interpreting anticholinergic drug exposure using existing scales due to the wide variability between the different scales.